2011
DOI: 10.19030/iber.v5i10.3517
|View full text |Cite
|
Sign up to set email alerts
|

How Women Are Depicted In Ads? A Content Analysis Study With Brazilian Advertisements

Abstract: The main purpose of this paper was to examine female roles portrayed by advertising. More specifically, the question that motivated this research project was: What messages about women have been given to society through advertisement? Have these portrayals been changed during the past decades? The study consisted of a systematic content analysis of Brazilian commercials from 1973 to 2000. The population from which this sample was drawn consisted of Brazilian commercials which got an award in international and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…However, presentation of gender-role portrayals in Brazil was not consistent with recent findings. Acevedo et al (2006) examined female portrayals in a content analysis of Brazilian television advertisements. Although their findings revealed that some specific images have changed lately (e.g., "ritualization of subordination" declined), in general, women in ads are still idealized and stereotyped as being dependent on men, physically beautiful and perfect, and unintelligent or irrational.…”
Section: Discussionmentioning
confidence: 99%
“…However, presentation of gender-role portrayals in Brazil was not consistent with recent findings. Acevedo et al (2006) examined female portrayals in a content analysis of Brazilian television advertisements. Although their findings revealed that some specific images have changed lately (e.g., "ritualization of subordination" declined), in general, women in ads are still idealized and stereotyped as being dependent on men, physically beautiful and perfect, and unintelligent or irrational.…”
Section: Discussionmentioning
confidence: 99%
“…The coding categories were based mainly on Goffman's [17] work. The authors concluded that "our results reveal portrayals (the stereotyped and idealized ones) which are impregnated by prejudice against women and insinuate a hidden trace of male domination" [16].…”
Section: Introductionmentioning
confidence: 90%
“…Acevedo et al [16] examined female roles portrayed in Brazilian advertisements which got an award in international and national festivals from 1973 to 2000. A total of ninety five pieces were selected.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some are comparative and of a longitudinal nature and have aimed to assess whether the roles of men and women have changed over time through content analysis or, on the contrary, have remained basically the same in similar or different cultures (cf. Acevedo et al 2006;Allan and Coltraine 1996;Baker 2005;Bretl and Cantor 1998;Ferrante et al 1988;Frith et al 2004;Lovdal 1989;Mager and Helgeson 2010;McArthur and Resko 1975;O'Donell and O'Donell 1978;Paek et al 2010;Signorelli et al 1994). These studies have all agreed on the unequal or biased depiction of male and female characters in TV commercials (Tsichla and Zotos 2013): that is, men normally outnumber women in TV programming (Coltrane and Messieno 2000;Signorelli and Leavs 1992) women are unequally portrayed in TV commercials (Ferrante et al 1988;Lovdal 1989), and are shown in the traditional or stereotyped roles of mothers and housewives (Courtney and Whipple 1983;Mager and Helgeson 2011;Tuchman 1978), while being placed 188 M. del Saz Rubio in the home rather than in outdoor, public or business settings (Milner and Collins 2000;Shrikhande 2003;Valls-Fernández and Martinez-Vincente 2007) or placed in decorative roles (Plakoyiannaki and Zotos 2009) and as low-income earners (Belkaoui and Belkaoui 1976).…”
Section: Introductionmentioning
confidence: 99%